Double-Blind, Randomized, Placebo-Controlled Trial of Individualized Homeopathic Medicines in Atopic Dermatitis in Adults: A Replication Trial with 6 Months' Follow-up - Mandal, Sanjukta; Ghosh, Shubhamoy; Das, Aakash Deep; Biswas, Bikash; Palanisamy, Chithra; Guha, Nilanjana; Maiti, Shukdeb; Dutta, Souvik; Singh, Navin Kumar; Koley, Munmun; Saha, Subhranil (Homeopathy, 2023)
Background Atopic dermatitis (AD) is a chronic relapsing and remitting inflammatory skin disease that can have a significant impact on quality of life. During the last four decades, a rising trend in AD has been observed in India. Homeopathic medicines are claimed to be beneficial in AD; however, convincing research evidence has been lacking. We compared the efficacy of individualized homeopathic medicines (IHMs) against placebos in the treatment of AD.Methods In this double-blind, randomized, placebo-controlled trial of 6 months' duration (n = 60), adult patients were randomized to receive either IHMs (n = 30) or identical-looking placebos (n = 30). All participants received concomitant conventional care, which included the application of olive oil and maintaining local hygiene. The primary outcome measure was disease severity using the Patient-Oriented Scoring of Atopic Dermatitis (PO-SCORAD) scale; secondary outcomes were the Atopic Dermatitis Burden Scale for Adults (ADBSA) and Dermatological Life Quality Index (DLQI) – all were measured at baseline and every month, up to 6 months. Group differences were calculated on the intention-to-treat sample.Results After 6 months of intervention, inter-group differences became statistically significant on PO-SCORAD, the primary outcome (−18.1; 95% confidence interval, −24.0 to −12.2), favoring IHMs against placebos (F1, 52 = 14.735; p <0.001; two-way repeated measures analysis of variance). Inter-group differences for the secondary outcomes favored homeopathy, but were overall statistically non-significant (ADBSA: F1, 52 = 0.019; p = 0.891; DLQI: F1, 52 = 0.692; p = 0.409).Conclusion IHMs performed significantly better than placebos in reducing the severity of AD in adults, though the medicines had no overall significant impact on AD burden or DLQI.
Keywords: atopic dermatitis; homeopathy; placebo; quality of life; randomized controlled trial